DIASTOLIC DYSFUNCTION OF THE RIGHT VENTRICLE IN CORONARY HEART DISEASE PATIENTS - O. G. Arkhipov; A. N. Sumin (Российский кардиологический журнал)
Aim. Evaluation of the prevalence of the right ventricle diastolic dysfunction (RVDD) in coronary heart disease patients (CHD), and factors associated with its diagnostics. material and methods. Totally, 691 CHD patient included (412 males) at the age 36-85  y.o. (mean  age  61,0 y.o.). Patients  were selected to 2 groups:  with saved diastolic RV function (n=478) and with RVDD (n=199). All participants  underwent echocardiography with diastolic function assessment of the left ventricle (LV) and RV in impulse-wave dopplerometry  of atrioventricular flows, spectral  tissue Doppler of the mitral and tricuspid anuli, and color-M-modal scan.Results. The prevalence  of diastolic dysfunction of RV in CHD patients  was 29%. Most significant was the decline of velocity of tricuspid flow in group 2, being 22% lower than group 1 (p<0,0001). From the diastolic part of spectrum of tricuspid annulus there was significant decrease of the velocity of its early diastolic motion еt in RVDD t patients by 16% (Z=4,5; p<0,0001). Relation е’t /а’t  significantly decreased in group 2 (p=0,001). Relation Еt /е’t increased significantly only in group 2, by 14% (p=0,001). The  independent factors  associated with RVDD were  age  (p=0,02),  diabetes (p=0,021), clinical picture of angina III functional class (p=0,00011), decrease of LV ejection fraction (p<0,0001)  and diastolic dysfunction of LV (LVDD)  (p<0,0001  and p=0,0069 with different parameters).Conclusion. RVDD was found in 29% CHD patients,  investigated  outpatient.  With RVDD there was association of age, diabetes, angina III class, decreased LV ejection fraction and LVDD. In RVDD assessment it is purposeful to apply complex approach with the parameters of intraventricular currents.